1989
DOI: 10.1007/bf00376803
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of seven species of filamentous fungi using the nitrate reductase gene of Aspergillus nidulans

Abstract: A gene transfer system originally developed for Fusarium oxysporum has been applied to seven species of filamentous fungi of agricultural and industrial importance. This transformation system relies on the selection of mutants deficient in nitrate reductase by positive screening. Such mutants were recovered easily in all the fungi tested--without mutagenic treatments--through their resistance to chlorate. They were transformed by a plasmid vector (pAN301) carrying the Aspergillus nidulans wild-type gene (niaD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(59 citation statements)
references
References 23 publications
0
57
1
Order By: Relevance
“…Media composition, M. grisea maintenance, transformation, and sexual crosses were as described (13,14). P1.2 (MAT1.2) and M4 (MAT1.1) are M. grisea strains from the Centre de Coopération Internationale en Recherche Agronomique pour le Développement (CIRAD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Media composition, M. grisea maintenance, transformation, and sexual crosses were as described (13,14). P1.2 (MAT1.2) and M4 (MAT1.1) are M. grisea strains from the Centre de Coopération Internationale en Recherche Agronomique pour le Développement (CIRAD).…”
Section: Methodsmentioning
confidence: 99%
“…pBLHYG plasmid is a pBL plasmid with the hph cassette from pCB1003 (20) cloned at its EcoRI site. M. grisea genomic DNA extractions were performed as described (13). Total RNA was extracted by using the hot acid͞phenol protocol (21).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, the niaD gene of A. nidulans, can complement NR-deficient strains of several other ascomycetous fungi (Daboussi et al 1989). The enzyme is strongly conserved through evolution and, as shown above, NR encoded by the P. infestans niaA gene contains all the conserved domains which are essential for enzyme activity.…”
Section: Comparison Of P Infestans Nr With That Of Other Organismsmentioning
confidence: 93%
“…This was done by transforming the P infestans niaA gene to a A. nidulans nia-mutant and analyzing the transformants for functional complementation of the NR deficiency. It has been shown that NR deficiency in several filamentous fungi, including some plant pathogens, can be complemented by the introduction of heterologous NR genes (Daboussi et al 1989;Whitehead et al 1989;Unkles et al 1989a,b). In a second approach to test oomycete regulatory sequences in a non-oomycete we used constructs containing promoter-GUS fusions.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by its black spore, by which it is named after (Daboussi, Djeballi et al 1989). Aspergillus niger is used for the commercial production of both small molecules and proteins.…”
Section: Aspergillus Niger Expression Systemmentioning
confidence: 99%